2014
DOI: 10.1093/inthealth/iht039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a novel community-based lifestyle intervention program on type 2 diabetes and cardiovascular risk in a resource-poor setting in the Dominican Republic

Abstract: Our pilot experience demonstrates the efficacy and feasibility of a novel, low-cost, community-based educational initiative to improve blood glucose control and reduce cardiovascular risk in individuals with type 2 diabetes or prediabetes. Replication of our model in other underserved areas could have a substantial impact on global health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 9 publications
0
40
0
Order By: Relevance
“…Lead community based cost effective and sustainable lifestyle modification and educational programs to be implemented that could lead to a significant reduction of DM, as well as other risk factors for CVD. 33 Dyslipidemia Elevated total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), triglycerides and low levels of high-density lipoprotein cholesterol (HDL-C) and their combination are important risk factors for MI and other vascular diseases. Latin America has experienced a significant nutritional transition, likely affected by international trade agreements and globalization; increasing production and consumption of preprocessed food, soybean and palm oil.…”
Section: Diabetesmentioning
confidence: 99%
“…Lead community based cost effective and sustainable lifestyle modification and educational programs to be implemented that could lead to a significant reduction of DM, as well as other risk factors for CVD. 33 Dyslipidemia Elevated total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), triglycerides and low levels of high-density lipoprotein cholesterol (HDL-C) and their combination are important risk factors for MI and other vascular diseases. Latin America has experienced a significant nutritional transition, likely affected by international trade agreements and globalization; increasing production and consumption of preprocessed food, soybean and palm oil.…”
Section: Diabetesmentioning
confidence: 99%
“…Sixty full texts were assessed for eligibility (Figure ). Seventeen met the criteria for inclusion and were extracted . The majority were conducted in Cuba (seven studies: 41%) and Trinidad and Tobago (five studies: 29%), the remainder in Jamaica (three studies: 18%), Guyana (one study: 6%) and Dominican Republic (one study: 6%) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies reported HbA1c, with four of the eight (50%) finding a significant improvement in HbA1c values (Table ) . One study found that HbA1c values significantly increased from baseline to 48 weeks .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations